PERANCANGAN SISTEM INFORMASI PELAYANAN UMKM TERPADU (SIPUT) PADA DINAS TENAGA KERJA, KOPERASI DAN UKM KOTA JAMBI - Puad , Lailyn; Mulyati, Sri; Ziqran Febian, Muhammad (FORTECH (Journal of Information Technology), 2024)
At the Jambi City Office of Manpower, Cooperatives and SMEs in the field of SMEs where the administration system and data collection of MSMEs are still carried out conventionally which still uses recording with books which of course takes up a lot of space to store data - data on MSME players in Jambi City. At the Jambi City Manpower, Cooperatives and SMEs Office in the SME sector, there is also no information media about news about MSMEs such as training and MSME assistance programs. Of course this is inefficient due to the large number of MSMEs domiciled in Jambi City per sub-district. In this case, the Jambi City Manpower, Cooperatives and UKM Office requires a system that can facilitate administration, data collection and media delivery of information about MSME training and MSME assistance programs to all business actors domiciled in Jambi City as well as a system that can manage MSME data in Jambi City. So that a system is needed that is able to manage administration and information services to MSME players in Jambi City. The information system design method used is the waterfall model with five stages, namely: Needs Analysis, System Design, Implementation, System testing and Maintenance. With this information system, it is hoped that it can make it easier for the Jambi City Manpower, Cooperatives and UKM Office to provide online information services and manage MSME data administration. This system is expected to improve the quality of MSMEs in Jambi City.